2001
DOI: 10.1007/3-540-44578-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino Cooling of Neutron Stars: Medium Effects

Abstract: Abstract. This review demonstrates that the neutrino emission from the dense hadronic component in neutron stars is subject to strong modifications due to collective effects in nuclear matter. With the most important in-medium processes incorporated in the cooling code an overall agreement with available soft X ray data can be easily achieved. With these findings so called "standard" and "non-standard" cooling scenarios are replaced by one general "nuclear medium cooling scenario" which relates slow and rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(118 citation statements)
references
References 68 publications
(223 reference statements)
0
118
0
Order By: Relevance
“…Neutrino emissivity Q ν may be strongly modified by in-medium (collective) effects at the high densities of neutron stars (see Voskresensky 2001, for a review). For instance, these effects may result in renormalization of electroweak interaction parameters.…”
Section: Remarks On In-medium Effectsmentioning
confidence: 99%
“…Neutrino emissivity Q ν may be strongly modified by in-medium (collective) effects at the high densities of neutron stars (see Voskresensky 2001, for a review). For instance, these effects may result in renormalization of electroweak interaction parameters.…”
Section: Remarks On In-medium Effectsmentioning
confidence: 99%
“…Based on the Fermi-liquid model, explicit expressions for (a) and (b) have been derived in Voskresensky (2001). In the latter article it has also been shown that for the medium modifications of D π the most important contribution to the charged current processes (modified Urca) originates from neutrino reactions of intermediate nucleon-loops coupled to the π for ρ ρ 0 /2.…”
Section: Nucleon-nucleon Bremsstrahlungmentioning
confidence: 99%
“…A more general approach to study medium modifications for weak processes that involve N N interactions is the Fermi-liquid theory of Migdal (1978) and Migdal et al (1990) (see also Voskresensky, 2001, and references therein). It assumes that the nucleons are only slightly excited above their Fermi sea such that all the processes occur in a narrow vicinity of the Fermi surface and that the vertices of the processes are dressed by N N correlations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations